KIDNEY LESIONS IN HIV-INFECTED PATIENTS - Andrushchak М. О. (International Journal of Medicine and Medical Research, 2019)
Introduction. HIV prevalence is one of the most important issues of contemporary medicine. Over a 30-year history of this disease more than 75 million people have been infected with HIV, nearly 30 million adults and children of died. In the future decades, its significance in world premature mortality rates continues to rise. The objective of the study was to establish clinical and laboratory features of kidney lesions in HIV infection. Methods. The study involved 292 HIV-infected patients, who were managed outpatiently at the Chernivtsi Regional AIDS Center. Taking into account the main markers of kidney lesions: persistent proteinuria and glomerular filtration rate <60 mL/min/1.73 m2, 48 persons were diagnosed with chronic kidney disease (CKD), which was very frequently accompanied by dysfunction of these organs. Results. Increasing proteinuria rate is accompanied by a significant renal dysfunction and more frequently is combined with arterial hypertension as well as hematuria without significant differences in the incidence of opportunistic diseases. The mean reciprocal correlation between the levels of proteinuria and glomerular filtration rate (r=-0.562, p<0.01), as well as between the levels of proteinuria and hemoglobin (r=-0.596, p<0.01) have been established as well. Conclusions. Kidney lesions in HIV-infected are most often characterized by tubulointerstitial lesions. At the same time, glomerular kidney lesion, which is much less common, is accompanied by a significantly higher level of HIV RNA.